Determinants Of Public Shopping Through E-Commerce in The Jabodetabek Area - Anwar Suhartono (LAFADZ JAYA Publisher, 2023)
In the digital era, shopping with e-commerce is a necessity for the community, especially the millennial generation who have high mobility. The purpose of this study was to examine the effect of the variables Customer Satisfaction, Technology Acceptance Model (TAM) and Product Quality on the decision to buy e-commerce products. The object of research is the living community in Jabodetabek area, with a design using descriptive quantitative. The research data source is primary data obtained by distributing questionnaires to respondents to the population of communities who live in Jabodetabek area with the sample selection technique using random sampling of 107 respondents. Data analysis used Structural Equation Modeling (SEM) with PLS 3.0 software. The research results prove that The Customer Satisfaction variable based on the statistical t value obtains a value of 0.174 < 1.96, so it can be stated that the Customer Satisfaction variable has no significant effect on the dependent variable Buying Decision.While based on the P-Value obtained 0.862 > 0.05, it means that the Customer Satisfaction variable has no significant effect on the dependent variable Buying Decision.The Technology Acceptance Model variable based on the statistical t value obtains a value of 2.99 > 1.96, so it can be stated that the Technology Acceptance Model variable has a significant effect on the dependent variable Buying Decision.While based on the P-Value obtained 0.003 < 0.05, it means that the Technology Acceptance Model variable has a significant effect on the dependent variable Buying Decision. The Product Quality variable based on the statistical t value obtained a value of 1.304 < 1.96, so it can be stated that the Product Quality variable has no significant effect on the dependent variable Buying Decision. While based on the P-Value obtained 0.193 > 0.05, it means that the Product Quality variable has no significant effect on the dependent variable Buying Decision.